Adjuvanted Schistosoma mansoni-Cathepsin B With Sulfated Lactosyl Archaeol Archaeosomes or AddaVax™ Provides Protection in a Pre-Clinical Schistosomiasis Model - Perera, Dilhan J.; Hassan, Adam S.; Jia, Yimei; Ricciardi, Alessandra; McCluskie, Michael J.; Weeratna, Risini D.; Ndao, Momar (Frontiers in Immunology, 2020)
Schistosomiasis threatens 800 million people worldwide. Chronic pathology manifests as hepatosplenomegaly, and intestinal schistosomiasis caused by Schistosoma mansoni can lead to liver fibrosis, cirrhosis, and blood in the stool. To assist the only FDA approved drug, praziquantel, in parasite elimination, the development of a vaccine would be of high value. S. mansoni Cathepsin B (SmCB) is a well documented vaccine target for intestinal schistosomiasis. Herein, we test the increased efficacy and immunogenicity of S. mansoni Cathepsin B (SmCB) when combined with sulfated lactosyl archaeol (SLA) archaeosomes or AddaVax™ (a squalene based oil-in-water emulsion). Both vaccine formulations resulted in robust humoral and cell mediated immune responses. Impressively, both formulations were able to reduce parasite burden greater than 40% (WHO standard) with AddaVax™ reaching 86.8%. Additionally, SmCB with both adjuvants were able to reduce granuloma size and the amount of larval parasite hatched from feces which would reduce transmission. Our data support SmCB as a target for S. mansoni vaccination; especially when used in an adjuvanted formulation.